2005
DOI: 10.1002/cpp.451
|View full text |Cite
|
Sign up to set email alerts
|

Stalking—perceptions and attitudes amongst helping professions. An EU cross‐national comparison

Abstract: This study examined recognition of and attitudes towards abnormal, persistent, unwanted attention, or stalking, in two professional groups closely involved in assisting the victims of this behaviour, i.e. police officers and general practitioners (GPs), in four European countries (Belgium, n = 185; UK, n = 118; Netherlands, n = 113; Italy, n = 100). Responses to standardized questions on systematically developed vignettes depicting various male-on-female stalking scenarios were examined in terms of responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…Still, while the terms 'stalking' and 'stalker' are commonly used and often misapplied in everyday life there is a considerable lack of awareness about what is actually stalking and what it involves not only in the general public but also among criminal justice system professionals and sometimes even victims (Kamphuis et al, 2005;Jordan et al, 2007;Tjaden, 2009). This is largely due to the elusive nature of the behaviour, its different depictions by the media and the lack of a globally accepted definition for the crime of stalking (Jagessar and Sheridan, 2004).…”
Section: Conceptualising Defining and Criminalising Stalking Definitmentioning
confidence: 99%
“…Still, while the terms 'stalking' and 'stalker' are commonly used and often misapplied in everyday life there is a considerable lack of awareness about what is actually stalking and what it involves not only in the general public but also among criminal justice system professionals and sometimes even victims (Kamphuis et al, 2005;Jordan et al, 2007;Tjaden, 2009). This is largely due to the elusive nature of the behaviour, its different depictions by the media and the lack of a globally accepted definition for the crime of stalking (Jagessar and Sheridan, 2004).…”
Section: Conceptualising Defining and Criminalising Stalking Definitmentioning
confidence: 99%
“…The factor structure identified by Kamphuis et al (2005), who conducted a principal component analysis of McKeon et al's (2009) SAQ, included eight factors. The authors explained the first three factors accounted for 35% of the common variance as stalking is a nuisance (α = .74), blaming the victim (α = .78), and stalking is flattery (α = .80).…”
Section: Reliability Of Previous Factor Structurementioning
confidence: 99%
“…Today, stalking remains an all too common experience (Balloni, Bisi, & Sette, 2012) and appears to be a worldwide phenomenon. However, beliefs and attitudes about stalking differ according to geographical, social, and cultural contexts (De Fazio & Galeazzi, 2004;Kamphuis et al, 2005), types of commonsense justice (Dennison & Thomson, 2002;Finkel, 1995), and legal contexts (Jagessar & Sheridan, 2004).…”
mentioning
confidence: 99%
“…Finally, it is also possible that negative attitudes about stalking may contribute to police inaction. Kamphuis et al (2005) found that a lack of decent knowledge about legislation on stalking, as well as a stereotype attitude towards stalking result in less action by the police.…”
mentioning
confidence: 99%
“…Some officers have reported that stalking is not a serious crime and that stalking was a domestic or private matter that was inappropriate for criminal justice intervention (Bradburn, 1992;Morris et al, 2000;Rupp, 2005;Spitzberg 2002). The trivialization of stalking by legal professionals has a major influence on their treatment of stalking victims (Kamphuis et al, 2005;Logan et al, 2006).…”
mentioning
confidence: 99%